Volume Fraction Dependent Wear Behavior of Titanium-Reinforced Aluminum Matrix Composites Manufactured by Melt Infiltration Casting - Gecu, Ridvan; Karaaslan, Ahmet (ASME, 2019)
This study aims to investigate the effect of volume fraction of commercially pure titanium (CP-Ti) on microstructural, mechanical, and tribological features of A356 aluminum matrix composites. Vacuum-assisted melt infiltration casting was performed to produce composites with 50%, 65%, 75%, and 80% CP-Ti contents. CP-Ti sawdusts were assembled under mechanical pressure in order to attain porous one-piece CP-Ti preforms which were infiltrated by A356 melt at 730 degrees C under 10(-5) Pa vacuum atmosphere. TiAl3 layer was formed at the interface between A356 and CP-Ti phases. Owing to increased diffusion time through decreased diffusion path length, both thickness and hardness of TiAl3 phase were increased with increasing CP-Ti ratio, whereas the best wear resistance was obtained at 65% CP-Ti ratio. The main reason for decrease in wear resistance of 75% and 80% CP-Ti reinforced composites was fragmentation of TiAl3 layer during wear process due to its excessively increased brittleness. Strongly bonded TiAl3 phase at the interface provided better wear resistance, while weakly bonded ones caused to multiply wear rate.
Keywords: Bimetal composite; wear; aluminum-titanium; melt infiltration casting; DRY SLIDING WEAR; MECHANICAL-PROPERTIES; MICROSTRUCTURAL CHARACTERIZATION; ABRASIVE WEAR; AL; GRAPHITE; AL2O3; ALLOY; TI; Engineering